Schwannoma of the upper lip: a 66-year single-center retrospective analysis in southern Brazilian population and literature cases review - Curra, Marina; Sant’Ana Filho, Manoel; Martins, Marco Antonio Trevizani; Romanini, Juliana; Carrard, Vinicius Coelho; Martins, Manoela Domingues (Journal of Oral Diagnosis, 2016)
Schwannoma is a benign tumor of neural origin. This condition is uncommon in the upper lip. The aim the present study was to perform an analysis of lip lesions at an oral pathology laboratory to determine the frequency of schwannoma of the upper lip and perform a literature review to correlate with the cases of this study. A retrospective analysis was performed at the oral pathology laboratory and the histopathological records from 1946 to 2012 were retrieved and organized in a database. Cases of schwannoma of the upper lip were identified and analyzed. Moreover, a literature review was performed on schwannomas found in this same anatomic site. In this period, 1195 lip lesions were diagnosed, among which four were cases of schwannoma on the upper lip (0,33%). Of these, 3 cases were in women; the mean age of patients was 45 years old. In all cases the clinical diagnosis hypothesis involved reactive lesion or benign neoplasm.The final diagnosis of schwannoma was obtained following the histopathological examination of the surgical specimens. This study emphasizes the low frequency of schwannoma in the upper lip and the importance of histological evaluation to define the final diagnosis which usually represents unexpected outcomes.